Respuesta :

Answer:

[tex]\displaystyle b_2=\frac{2A}{h}-b_1[/tex]

Step-by-step explanation:

Equation Solving

Given the formula:

[tex]\displaystyle A=\frac{1}{2}h(b_1+b_2)[/tex]

It's required to solve it for b2.

First, we eliminate denominators by multiplying by 2:

[tex]\displaystyle 2A=h(b_1+b_2)[/tex]

Divide by h:

[tex]\displaystyle \frac{2A}{h}=b_1+b_2[/tex]

Subtract b1:

[tex]\displaystyle \frac{2A}{h}-b_1=b_2[/tex]

Write the new formula:

[tex]\boxed{\displaystyle b_2=\frac{2A}{h}-b_1}[/tex]

ACCESS MORE